PENGARUH KEPERCAYAAN, PERSEPSI RISIKO, DAN KEAMANAN TERHADAP MINAT BELI KONSUMEN PADA E-COMMERCE SHOPEE - Anis Purdianawati; Rafidah Rafidah (Jurnal Cakrawala Ilmiah, 2023)
This study aims to determine the effect of trust, perceived risk and security on the buying interest of students of the Islamic economics and business faculty (consumers), this research is quantitative. The sample used was 309 respondents. Based on the results of the study, there is one variable that does not have a significant effect on buying interest in Islamic economics and business students (consumers), namely the risk perception variable, while the other two variables, namely trust and security, have a positive and significant effect on the interest of students in the Islamic economics and business faculty (consumers), Simultaneously there is a significant influence between trust, perceived risk and security. The value of Adjusted R Square (R2) is 0.538 or 53.8%, which means that the influence of the independent variable on the dependent variable gives an effect of 53.8%% and the remaining 46.2% is influenced by other variables outside of this study.